Developing a measurement scale for employee engagement: a validation study in a South Korean context. Issue 5 (14th July 2021) - So, Byung Han; Kim, Ji Hyun; Ro, Yun Jeong; Song, Ji Hoon
Abstract : Purpose: The purpose of this paper is to develop a reliable and valid measurement scale of employee engagement that can be used in human resources departments in any industry field. Design/methodology/approach: This study used the measurement development process with three steps. The first step was to generate items for measuring employee engagement. For this reason, the authors proposed an integrated conceptual model based on the results of a literature review and justify the concepts from self-determination theory and person-environment fit theory as the theoretical foundation. The second step was to determine the types of questions suitable for measurement, examining the content validity. Content validity was conducted two times by the group, academic experts and business practitioners. The last step was to examine the exploratory factor analysis (EFA), confirmatory factor analysis (CFA), multi-group analysis and reliability with 352 survey responses from the South Korean business context. Findings: Findings of the measurement scale development procedure, i.e. employee engagement, should be managed in a balanced manner in all dimensions, as it is composed of four dimensions (person engagement, work engagement, organization engagement and relation engagement) and 16 sub-factors. Additionally, organization engagement was the major factor among the four dimensions of employee engagement with the highest variance explanation. From the statistical standpoint, the employee engagement scale (EES) is possible to use in any industry field because it demonstrated not only content validity and internal consistency reliability but also the three steps of factor analysis (EFA, CFA and multi-group analysis). Research limitations/implications: This survey was conducted with an assistant manager located in Korea. Therefore, it will be necessary to analyze both leader and employee engagement for those who live in foreign countries. The EES is useful to leaders and human resource managers because it is applicable to managing engagement levels of employees and fosters customized training programs. Originality/value: This is the first study to develop measurement tools for employee engagement in South Korea. In addition, most studies demonstrated that individual feeling was valued to drive employee engagement. This research, however, proposes an extended concept of employee engagement for four dimensions (person, work, relation and organization) and emphasizes the important relationship between individuals and colleagues in an organization. Based on these results, a theoretically integrated model of employee engagement was developed and a practically valid measurement tool for capturing comprehensive domains of employee engagement was proposed.